Dynamic state of plasmid genomic architectures resulting from XerC/D-mediated site-specific recombination in Acinetobacter baumannii Rep_3 superfamily resistance plasmids carrying blaOXA-58- and TnaphA6-resistance modules - Giacone, Lucía; Cameranesi, M. Marcela; Sanchez, Rocío I.; Limansky, Adriana S.; Morán-Barrio, Jorgelina; Viale, Alejandro M. (Frontiers in Microbiology, 2023)
The acquisition of blaOXA genes encoding different carbapenem-hydrolyzing class-D β-lactamases (CHDL) represents a main determinant of carbapenem resistance in the nosocomial pathogen Acinetobacter baumannii. The blaOXA-58 gene, in particular, is generally embedded in similar resistance modules (RM) carried by plasmids unique to the Acinetobacter genus lacking self-transferability. The ample variations in the immediate genomic contexts in which blaOXA-58-containing RMs are inserted among these plasmids, and the almost invariable presence at their borders of non-identical 28-bp sequences potentially recognized by the host XerC and XerD tyrosine recombinases (pXerC/D-like sites), suggested an involvement of these sites in the lateral mobilization of the gene structures they encircle. However, whether and how these pXerC/D sites participate in this process is only beginning to be understood. Here, we used a series of experimental approaches to analyze the contribution of pXerC/D-mediated site-specific recombination to the generation of structural diversity between resistance plasmids carrying pXerC/D-bounded blaOXA-58- and TnaphA6-containing RM harbored by two phylogenetically- and epidemiologically-closely related A. baumannii strains of our collection, Ab242 and Ab825, during adaptation to the hospital environment. Our analysis disclosed the existence of different bona fide pairs of recombinationally-active pXerC/D sites in these plasmids, some mediating reversible intramolecular inversions and others reversible plasmid fusions/resolutions. All of the identified recombinationally-active pairs shared identical GGTGTA sequences at the cr spacer separating the XerC- and XerD-binding regions. The fusion of two Ab825 plasmids mediated by a pair of recombinationally-active pXerC/D sites displaying sequence differences at the cr spacer could be inferred on the basis of sequence comparison analysis, but no evidence of reversibility could be obtained in this case. The reversible plasmid genome rearrangements mediated by recombinationally-active pairs of pXerC/D sites reported here probably represents an ancient mechanism of generating structural diversity in the Acinetobacter plasmid pool. This recursive process could facilitate a rapid adaptation of an eventual bacterial host to changing environments, and has certainly contributed to the evolution of Acinetobacter plasmids and the capture and dissemination of blaOXA-58 genes among Acinetobacter and non-Acinetobacter populations co-residing in the hospital niche.